Preparation method of spherical powder of particle-reinforced aluminum matrix composite material for 3D printing

Through ball mill mixing and micro-oxygen sintering combined with mechanical grinding and deoxygenation treatment, the uneven mixing problem of particle-enhanced aluminum-based composite materials was solved, and a spherical powder with high density and uniform distribution was prepared, which improved the forming stability and performance of 3D printing.

CN119870450BActive Publication Date: 2025-08-01江西国创院新材料有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510128950.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-08-01
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

The prior art has problems of uneven mixing, uneven tissue and poor interface bonding when preparing particulate reinforced aluminum composite materials, which affects the comprehensive performance of 3D printed parts.

Method used

The slurry is prepared by ball mill mixing, and the granulation is made by centrifugal spray-drying, combined with micro-oxygen sintering and mechanical grinding to assist chemical dissolution and deoxygenation treatment to prepare spherical powders with high density and uniform component distribution.

Benefits of technology

The uniform mixing and high density of particle-enhanced aluminum-based composite powder is achieved, the forming stability and performance of laser 3D printing is improved, and the preparation process flow is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119870450B_ABST
    Figure CN119870450B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing spherical powder of particle-reinforced aluminum matrix composite for 3D printing, belonging to the technical field of metal additive manufacturing. By utilizing the characteristic that an oxide film is easily formed on the surface of aluminum alloy, the present invention densifies the agglomerates of aluminum matrix composite prepared by spray drying and spheronization granulation through micro-oxygen-containing sintering, and then conducts deoxidation through mechanical grinding assisted chemical corrosion to obtain spherical powder of particle-reinforced aluminum matrix composite suitable for laser 3D printing, which has high sphericity, high density and low oxygen content. The spherical powder of particle-reinforced aluminum matrix composite prepared by the present invention has the characteristics of good sphericity and fluidity, high density, uniform distribution of components, high laser absorption rate, etc., is suitable for 3D printing technologies such as laser powder bed fusion, laser directed energy deposition and laser cladding, and the preparation process flow is simple, has no special requirements for equipment, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal additive manufacturing, and particularly relates to a method for preparing spherical powder of particle-reinforced aluminum matrix composite material for 3D printing. Background Art

[0002] Compared with aluminum alloys, particle-reinforced aluminum matrix composites have become an important development direction of lightweight metal structural materials due to their higher specific strength, higher wear resistance, lower thermal expansion coefficient, and better high-temperature resistance performance, and have broad application prospects in the fields of aerospace, electronic information, transportation, etc. Currently, the main preparation methods of particle-reinforced aluminum matrix composites include powder metallurgy, stir casting, pressure infiltration, and spray deposition. These preparation technologies all have problems such as complex process flow, long manufacturing cycle, and the need for secondary processing, and it is difficult to prepare large-sized parts and complex structural parts, which limits the exertion of the superior performance of particle-reinforced aluminum matrix composites. With the rapid development of fields such as aerospace and electronic packaging, higher requirements are put forward for the performance of parts, and the demand for parts with complex structures has increased rapidly. Developing short-process, near-net-shape 3D printing technology is an important way to solve the forming problems of particle-reinforced aluminum matrix composites and further broaden their application fields.

[0003] The 3D printing preparation technologies applicable to particle-reinforced aluminum matrix composites mainly include laser powder bed fusion, laser directed energy deposition, and laser cladding, etc. The principle of laser 3D printing forming is to use a high-energy laser beam to melt and rapidly solidify metal powder according to contour data, and realize the melting-solidification stacking forming of three-dimensional parts by layer-by-layer powder spreading or coaxial powder feeding. The quality of the raw material powder directly affects the forming process and the properties of the formed parts of laser 3D printing. Usually, the raw material powder for laser 3D printing must simultaneously meet the requirements of high sphericity, high density, low oxygen content, good fluidity, and high apparent density. High-fluidity powder is the basic key raw material for 3D printing aluminum matrix composites and also the greatest value.

[0004] At present, the preparation of particle-reinforced aluminum matrix composites by laser 3D printing mostly adopts direct mixing of powders, that is, directly mechanically mixing gas-atomized spherical aluminum or aluminum alloy powders with ceramic reinforcement phase powders. Since the densities and particle sizes of ceramic particle powders such as WC, TiB2, and Y2O3 are quite different from those of aluminum matrix powders, problems such as uneven mixing and fine powder agglomeration often occur during the premixing process, resulting in uneven microstructure of the printed parts, poor interfacial bonding between the second phase and the matrix, and seriously affecting the comprehensive performance of the printed parts. Summary of the Invention

[0005] The purpose of the present invention is to provide a method for preparing spherical powder of particle-reinforced aluminum matrix composite material for 3D printing with good sphericity and fluidity, high density, uniform component distribution, and low oxygen content.

[0006] To achieve the above-mentioned invention object, the present invention provides the following technical solutions: A preparation method of spherical powder of particle-reinforced aluminum matrix composite material for 3D printing, comprising the following steps:

[0007] Step 1: Using the powders of each component as raw materials, according to the composition design ratio of the particle-reinforced aluminum matrix composite material, mix the raw material powders with anhydrous ethanol, dispersant, and binder by ball milling to prepare a stable slurry with a solid content of 40% - 80%, and perform spray drying and spheroidization granulation on the slurry through a centrifugal spray drying device.

[0008] Step 2: Perform sintering heat treatment on the spheroidized agglomerated powder obtained in Step 1 under a protective atmosphere containing trace oxygen, with a sintering temperature of 550 - 960 °C, a holding time of 30 - 240 minutes, and the sintering atmosphere pressure being normal pressure.

[0009] Step 3: Crush and classify the sintered block, add the powder within the target particle size range and an alkaline deoxidizer into a stirring ball milling device, and perform mechanical grinding-assisted chemical corrosion deoxidation treatment.

[0010] Step 4: Separate the powder after deoxidation treatment from the deoxidizer and grinding balls, wash it with acid and then wash it with anhydrous ethanol 2 - 3 times, and obtain spherical powder of particle-reinforced aluminum matrix composite material for 3D printing after vacuum drying.

[0011] Further, the aluminum alloy of the matrix component is selected from one of 1xxx series aluminum alloy, 2xxx series aluminum alloy, 3xxx series aluminum alloy, 4xxx series aluminum alloy, 5xxx series aluminum alloy, 6xxx series aluminum alloy, 7xxx series aluminum alloy, 8xxx series aluminum alloy, 9xxx series aluminum alloy; the particle-reinforced phase component is selected from one or more of TiB2, ZrB2, BN, B4C, SiC, TiC, WC, Al3BC, AlN, TiN, Si3N4, Al2O3, Y2O3, TiO2, SiO2, ZrO2, MgO, diamond;

[0012] Further, in Step 1, the particle size of the pure aluminum or aluminum alloy matrix component powder is 1 - 15 μm, and the particle size of the particle-reinforced phase component powder is selected according to the material properties and does not exceed 20 μm.

[0013] Further, in Step 1, the composition design mass ratio of the particle-reinforced aluminum matrix composite material is matrix component: particle-reinforced phase component = 10:90 - 99.5:0.5.

[0014] Further, in Step 2, the sintering atmosphere is nitrogen or argon containing trace oxygen, and the oxygen content is 0.5 - 2.0 %VOL.

[0015] Further, in Step 3, the alkaline deoxidizer is an ethanol aqueous solution of sodium hydroxide, where the NaOH concentration is 10 - 25 g / L, and the volume ratio of ethanol to water in the solvent is 1:9 - 3:7.

[0016] Further, in Step 3, the deoxidation treatment reaction temperature is 25 - 40 °C, and the deoxidation time is 8 - 30 min.

[0017] Further, in Step 4, the pickling solution is nitric acid with a mass concentration of 15 - 35%, the pickling immersion temperature is 25 - 40 °C, and the treatment time is 0.5 - 2 minutes.

[0018] In Step 1 of the present invention, the dispersant is one of polyethylene glycol, polyethylene, and polypropylene which are conventional in the art, the binder is one of polyvinyl alcohol and polytetrafluoroethylene which are conventional in the art, and the classification is carried out by conventional screening or air classification.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention uses ball milling to mix and prepare the slurry, which can effectively solve the problems of component segregation and agglomeration caused by the density and size differences of different powders, realize the uniform mixing of the matrix component and the particle-reinforced component, and obtain spherical aluminum matrix composite agglomerates with uniform composition and dispersed distribution of the reinforcing phase particles after spray drying.

[0021] (2) Utilizing the characteristic that an oxide film is easily formed on the surface of aluminum alloy, the present invention uses micro-oxygen sintering to improve the density of the aluminum matrix composite powder particles. By introducing a certain concentration of oxygen into the sintering atmosphere, when the sintering temperature is higher than the melting point of the aluminum matrix, an oxide film will be formed on the surface of the molten pellets, liquid-phase sintering occurs inside the molten pellets, and the outside remains spherical under the action of the surface tension of the oxide film. This technical measure can significantly improve the density of the powder particles while effectively preventing adhesion and sintering between the particles, thereby realizing the independent sintering of the aluminum matrix composite powder particles, inheriting the spherical morphology of the spray-dried granulated powder to the greatest extent, and ensuring the dispersibility and fluidity of the aluminum matrix composite powder.

[0022] (3) The present invention conducts deoxidation treatment on the sintered powder by mechanical grinding assisted by chemical etching to reduce the oxygen content of the composite powder and obtain spherical powder of particle-reinforced aluminum matrix composite for 3D printing.

[0023] (4) The spherical powder of the particle-reinforced aluminum matrix composite prepared by the present invention has a rough surface, which can significantly improve the laser absorption rate of the powder, enhance the energy efficiency of laser 3D printing additive manufacturing, and ensure the stable progress of the printing process.

[0024] (5) The preparation process flow of the method of the present invention is simple, there are no special equipment and tooling requirements, and industrial production can be carried out using conventional powder metallurgy equipment. Description of the Drawings

[0025] Figure 1SEM images of 20wt.% SiC / Al spherical powder prepared in Example 1 ((a) low magnification, (b) high magnification).

[0026] Figure 2 SEM images of 40wt.% WC / AlSi10Mg spherical powder prepared in Example 2 ((a) low magnification, (b) high magnification).

[0027] Figure 3 SEM image of 20wt.% SiC / Al spherical powder prepared in Comparative Example 1.

[0028] Figure 4 SEM image of 20wt.% SiC / Al spherical powder prepared in Comparative Example 2. Detailed implementation manners

[0029] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0030] Example 1: Prepare 20wt.% SiC / Al spherical powder with a size of 15 - 53 µm for 3D printing.

[0031] Weigh 1200 g of pure aluminum powder with an average particle size of 5 µm and 300 g of SiC powder with an average particle size of 3 µm according to the mass ratio of Al:SiC = 80:20, and ball mill them with 1227 g of absolute ethanol, 30 g of polyethylene glycol and 1.5 g of polyvinyl alcohol to prepare a stable slurry with a solid content of 55%. Then, spray dry and spheroidize the slurry through a centrifugal spray drying device. The spray drying process is as follows: inlet air temperature 160 °C, atomizer rotation speed 16,000 rpm. Sinter the spheroidized pellet powder in an argon atmosphere with an oxygen content of 1% VOL. The sintering process is as follows: hold at 700 °C for 120 min. After cooling, crush the sintered product, pass it through a 270-mesh sieve, take the undersize for air classification, and obtain 20 wt.% SiC / Al sintered powder in the particle size range of 15 - 53 µm. Add the SiC / Al sintered powder and a NaOH ethanol aqueous solution with a concentration of 20 g / L (the volume ratio of solvent alcohol / water is 3:7) into a stirring ball mill device for mechanical grinding-assisted chemical corrosion deoxidation treatment. The deoxidation treatment process is as follows: reaction temperature 25 °C, stirring ball mill rotation speed 100 rpm, ball milling time 20 min. Separate the powder after deoxidation treatment from the deoxidizer and grinding balls by screening, soak it in a 20% mass concentration nitric acid solution at 30 °C for 1 min, then wash it 3 times with absolute ethanol, and finally place it in a vacuum drying oven for vacuum drying at 80 °C for 5 h to obtain 20 wt.% SiC / Al spherical powder with a particle size of 15 - 53 µm for 3D printing. The morphology and properties of the spherical powder of the particle-reinforced aluminum matrix composite material for 3D printing are respectively as Figure 1 shown in Table 1.

[0032] Table 1 Properties of 15 - 53 µm 20 wt.% SiC / Al spherical powder prepared in Example 1

[0033] Powder composition <![CDATA[Density (g / cm 3 )]]> <![CDATA[Bulk density (g / cm 3 )]]> Flowability (s / 50g) Oxygen content Particle size distribution 20wt.% SiC / Al 2.69 1.43 98.63 0.0519% <![CDATA[D 10 = 19.2 µm D 50 = 33.8 µm D 90 = 50.2 µm]]>

[0034] Example 2: Prepare 40 wt.% WC / AlSi10Mg spherical powder with a particle size of 53 - 125 µm for 3D printing.

[0035] Weigh 1200 g of AlSi10Mg powder with an average particle size of 10 µm and 800 g of WC powder with an average particle size of 1 µm according to the mass ratio of AlSi10Mg:WC = 60:40, and ball mill them with 1077 g of absolute ethanol, 40 g of polyethylene and 2 g of polyvinyl alcohol to prepare a stable slurry with a solid content of 65%. Then, spray dry and spheroidize the slurry through a centrifugal spray drying device. The spray drying process is as follows: inlet air temperature 170 °C, atomizer speed 10000 rpm. Sinter the spheroidized pellet powder in an argon atmosphere with an oxygen content of 0.5% VOL. The sintering process is as follows: hold at 900 °C for 150 min. After cooling, crush the sintered product and screen it through a -120 to +270 mesh sieve to obtain 40 wt.% WC / AlSi10Mg sintered powder with a particle size range of 53 - 125 µm. Add the WC / AlSi10Mg sintered powder and a NaOH ethanol aqueous solution with a concentration of 10 g / L (the volume ratio of solvent alcohol / water is 2:8) into a stirring ball mill device for mechanical grinding-assisted chemical corrosion deoxidation treatment. The deoxidation treatment process is as follows: reaction temperature 30 °C, stirring ball mill speed 130 rpm, ball milling time 10 min. Separate the powder after deoxidation treatment from the deoxidizer and grinding balls by screening, soak it in a 30% mass concentration nitric acid solution at 30 °C for 30 s, then wash it 3 times with absolute ethanol, and finally place it in a vacuum drying oven and dry it under vacuum at 80 °C for 5 h to obtain 40 wt.% WC / AlSi10Mg spherical powder with a particle size of 53 - 125 µm for 3D printing. The morphology and properties of the spherical powder of the particle-reinforced aluminum matrix composite material for 3D printing are respectively as Figure 2 shown in Table 2.

[0036] Table 2 Properties of 53 - 125 µm 40 wt.% WC / AlSi10Mg spherical powder prepared in Example 2

[0037] Powder composition <![CDATA[Density (g / cm 3 )]]> <![CDATA[Bulk density (g / cm 3 )]]> Flowability (s / 50g) Oxygen content Particle size distribution 40wt.% WC / AlSi10Mg 3.87 2.10 82.57 0.0475% <![CDATA[D 10 = 57.8 µm D 50 = 97.2 µm D 90 = 113.7 µm]]>

[0038] Example 3: Prepare 10 wt.% Y2O3 / Al spherical powder with a particle size of 25 - 75 µm for 3D printing.

[0039] Weigh 900 g of pure aluminum powder with an average particle size of 10 µm and 100 g of Y2O3 powder with an average particle size of 0.5 µm according to the mass ratio of Al:Y2O3 = 90:10, and ball mill them with 667 g of absolute ethanol, 25 g of polyethylene glycol and 1 g of polytetrafluoroethylene to prepare a stable slurry with a solid content of 60%. Then, spray dry and spheroidize the slurry through a centrifugal spray drying device. The spray drying process is as follows: inlet air temperature 160 °C, atomizer speed 12000 rpm. Sinter the spheroidized pellet powder in a nitrogen atmosphere with an oxygen content of 0.5% VOL. The sintering process is as follows: keep the temperature at 800 °C for 125 min. After cooling, crush the sintered product, pass it through a 200-mesh sieve, take the undersize for air classification, and obtain 10 wt.% Y2O3 / Al sintered powder with a particle size range of 25 - 75 µm. Add the Y2O3 / Al sintered powder and a NaOH ethanol aqueous solution with a concentration of 10 g / L (the volume ratio of solvent alcohol / water is 2:8) into a stirring ball mill device for mechanical grinding-assisted chemical corrosion deoxidation treatment. The deoxidation treatment process is as follows: reaction temperature 30 °C, stirring ball mill speed 120 rpm, ball milling time 10 min. Separate the deoxidized powder from the deoxidizer and grinding balls by screening, soak it in a 30% mass concentration nitric acid solution at 30 °C for 30 s, then wash it twice with absolute ethanol, and finally place it in a vacuum drying oven at 80 °C for vacuum drying for 5 h to obtain 10 wt.% Y2O3 / Al spherical powder with a particle size of 25 - 75 µm for 3D printing. The properties of the spherical powder of the particle-reinforced aluminum matrix composite material for 3D printing are shown in Table 3.

[0040] Table 3 Properties of 25 - 75 µm 10 wt.% Y2O3 / Al spherical powder prepared in Example 3

[0041] Powder composition <![CDATA[Density (g / cm 3 )]]> <![CDATA[Bulk density (g / cm 3 )]]> Flowability (s / 50g) Oxygen content Particle size distribution <![CDATA[10wt.% Y2O3 / Al]]> 2.73 1.42 88.13 0.0581% <![CDATA[D 10 =29.3 µmD 50 =56.1 µmD 90 =69.7 µm]]>

[0042] Comparative Example 1: Prepare 20 wt.% SiC / Al spherical powder with a particle size of 15 - 53 µm for 3D printing.

[0043] Weigh 1200 g of pure aluminum powder with an average particle size of 5 µm and 300 g of SiC powder with an average particle size of 3 µm according to the mass ratio of Al:SiC = 80:20, and ball mill them with 1227 g of absolute ethanol, 30 g of polyethylene glycol and 1.5 g of polyvinyl alcohol to prepare a stable slurry with a solid content of 55%. Then, spray dry and spheroidize the slurry through a centrifugal spray drying device. The spray drying process is as follows: inlet air temperature 160 °C, atomizer rotation speed 16,000 rpm. Sinter the spheroidized pellet powder in a pure argon atmosphere. The sintering process is as follows: hold at 700 °C for 120 min. After cooling, crush the sintered product, pass it through a 270-mesh sieve, take the material under the sieve for air classification to obtain 20 wt.% SiC / Al sintered powder in the particle size range of 15 - 53 µm. Add the SiC / Al sintered powder and a NaOH ethanol aqueous solution with a concentration of 20 g / L (the volume ratio of solvent alcohol / water is 3:7) into a stirring ball mill device for mechanical grinding-assisted chemical corrosion deoxidation treatment. The deoxidation treatment process is as follows: reaction temperature 25 °C, stirring ball mill rotation speed 100 rpm, ball milling time 20 min. Separate the powder after deoxidation treatment from the deoxidizer and grinding balls through screening, soak it in a 20% mass concentration nitric acid solution at 30 °C for 1 min, then wash it 3 times with absolute ethanol, and finally place it in a vacuum drying oven for vacuum drying at 80 °C for 5 h to obtain 15 - 53 µm 20 wt.% SiC / Al spherical powder. The morphology and properties of the spherical powder of this particle-reinforced aluminum matrix composite are respectively as Figure 3 shown in Table 4.

[0044] Table 4 Properties of 15 - 53 µm Al-20 wt.% SiC spherical powder prepared in Comparative Example 1

[0045] Powder composition <![CDATA[Density (g / cm 3 )]]> <![CDATA[Bulk density (g / cm 3 )]]> Flowability (s / 50g) Oxygen content Particle size distribution 20wt.% SiC / Al 1.72 Unable to pass the standard loopholes No flowability 0.0631% <![CDATA[D 10 = 20.2 µm D 50 = 39.7 µm D 90 = 63.5 µm]]>

[0046] Compared with Example 1, in Comparative Example 1, sintering was carried out in a pure argon atmosphere without oxygen. At this time, serious liquid-phase sintering adhesion occurred between the spherical aluminum matrix composite powder particles, resulting in poor sphericity and a significant reduction in the sphericity rate of the powder, seriously affecting the fluidity and loose bulk density of the powder.

[0047] Comparative Example 2: Prepare 15 - 53 µm 20 wt.% SiC / Al spherical powder for 3D printing.

[0048] Weigh 1200 g of pure aluminum powder with an average particle size of 5 µm and 300 g of SiC powder with an average particle size of 3 µm according to the mass ratio of Al:SiC = 80:20, and ball-mill them with 1227 g of absolute ethanol, 30 g of polyethylene glycol, and 1.5 g of polyvinyl alcohol to prepare a stable slurry with a solid content of 55%. Then, spray-dry and spheroidize the slurry through a centrifugal spray-drying device. The spray-drying process is as follows: inlet air temperature 160 °C, atomizer rotation speed 16,000 rpm. Sinter the spheroidized pellet powder in an argon atmosphere with an oxygen content of 5% VOL. The sintering process is as follows: hold at 700 °C for 120 min. After cooling, crush the sintered product, pass it through a 270-mesh sieve, take the undersize for air classification, and obtain 20 wt.% SiC / Al sintered powder in the particle size range of 15 - 53 µm. Add the SiC / Al sintered powder and a 20 g / L NaOH ethanol aqueous solution (solvent alcohol / water volume ratio is 3:7) into a stirring ball-mill device for mechanical grinding-assisted chemical corrosion deoxidation treatment. The deoxidation treatment process is as follows: reaction temperature 25 °C, stirring ball-mill rotation speed 100 rpm, ball-mill time 20 min. Separate the powder after deoxidation treatment from the deoxidizer and grinding balls by screening, soak it in a 20% mass concentration nitric acid solution at 30 °C for 1 min, then wash it 3 times with absolute ethanol, and finally place it in a vacuum drying oven for vacuum drying at 80 °C for 5 h to obtain 15 - 53 µm 20 wt.% SiC / Al spherical powder. The morphology and properties of the spherical powder of this particle-reinforced aluminum matrix composite are respectively as Figure 4 shown in Table 5.

[0049] Table 5 Properties of 15 - 53 µm 20 wt.% SiC / Al spherical powder prepared in Comparative Example 2

[0050] Powder composition <![CDATA[Density (g / cm 3 )]]> <![CDATA[Bulk density (g / cm 3 )]]> Flowability (s / 50g) Oxygen content Particle size distribution 20wt.% SiC / Al 1.33 0.78 141.21 0.0504% <![CDATA[D 10 =18.6 µmD 50 =35.1 µmD 90 =49.3 µm]]>

[0051] Compared with Example 1, in Comparative Example 2, sintering was carried out in an argon atmosphere with a high oxygen content, and the surface of the sintered powder was severely oxidized. After deoxidation treatment, the surface of the aluminum matrix composite powder particles was loose and porous, resulting in a decrease in particle density and an increase in surface roughness, seriously affecting the use performance of the powder.

[0052] Comparative Example 3: Prepare 15 - 53 µm 20 wt.% SiC / Al spherical powder for 3D printing.

[0053] Weigh 1200 g of pure aluminum powder with an average particle size of 5 µm and 300 g of SiC powder with an average particle size of 3 µm according to the mass ratio of Al:SiC = 80:20, and ball mill them with 1227 g of absolute ethanol, 30 g of polyethylene glycol, and 1.5 g of polyvinyl alcohol to prepare a stable slurry with a solid content of 55%. Then, spray dry and spheroidize the slurry through a centrifugal spray drying device. The spray drying process is as follows: inlet air temperature is 160 °C, and the atomizer rotation speed is 16000 rpm. Sinter the spheroidized pellet powder in an argon atmosphere with an oxygen content of 1% VOL. The sintering process is as follows: hold at 700 °C for 120 min. After cooling, crush the sintered product, pass it through a 270-mesh sieve, and take the undersize for air classification to obtain 20 wt.% SiC / Al sintered powder in the particle size range of 15 - 53 µm. The properties of the spherical powder of this aluminum matrix composite are shown in Table 6.

[0054] Table 6 Properties of 15 - 53 µm 20 wt.% SiC / Al spherical powder prepared in Comparative Example 3

[0055] Powder composition <![CDATA[Density (g / cm 3 )]]> <![CDATA[Bulk density (g / cm 3 )]]> Flowability (s / 50g) Oxygen content Particle size distribution 20wt.% SiC / Al 2.31 1.17 103.22 1.2279% <![CDATA[D 10 = 17.8 µm D 50 = 32.9 µm D 90 = 49.1 µm]]>

[0056] Compared with Example 1, in Comparative Example 3, sintering is carried out in an argon atmosphere with an oxygen content of 1%, without mechanical grinding-assisted chemical corrosion deoxidation treatment. The oxygen content of the obtained powder is too high to meet the requirements of laser 3D printing for raw material powder.

[0057] The preferred embodiments of this patent have been described in detail, but this patent is not limited to the above embodiments. Within the scope of knowledge possessed by ordinary technicians in the art, various changes can be made without departing from the purpose of this patent.

Claims

1. A preparation method of spherical powder of particle-reinforced aluminum matrix composite material for laser 3D printing, characterized in that: The described particle-reinforced aluminum matrix composite material is composed of a pure aluminum or aluminum alloy matrix component and a particle reinforcement phase component. The preparation method of the spherical powder comprises the following steps: Step 1: Using the powders of each component as raw materials, according to the composition design ratio of the particle-reinforced aluminum matrix composite material, ball-mill and mix the raw material powders with absolute ethanol, a dispersant, and a binder to prepare a stable slurry with a solid content of 40% to 80%. Spray-dry and spheroidize granulate the slurry through a centrifugal spray drying device; Step 2: Perform sintering heat treatment on the spheroidized pellets obtained in Step 1 under a protective atmosphere containing trace oxygen. The sintering temperature is 550 to 960 °C, the holding time is 30 to 240 minutes, the sintering atmosphere pressure is normal pressure, and the oxygen content is 0.5 to 2.0 %VOL; Step 3: Crush and classify the sintered block obtained in Step 2. Add the powder within the target particle size range and an alkaline deoxidizer into a stirring ball mill device, and perform mechanical grinding-assisted chemical corrosion deoxidation treatment; Step 4: Separate the powder after deoxidation treatment from the deoxidizer and grinding balls. Soak and pickle it, then wash it with absolute ethanol 2 to 3 times, and obtain spherical powder of the particle-reinforced aluminum matrix composite material for 3D printing after vacuum drying.

2. The preparation method of the spherical powder of the particle-reinforced aluminum matrix composite material for laser 3D printing according to claim 1, characterized in that: The aluminum alloy of the matrix component is selected from one of 1xxx series aluminum alloy, 2xxx series aluminum alloy, 3xxx series aluminum alloy, 4xxx series aluminum alloy, 5xxx series aluminum alloy, 6xxx series aluminum alloy, 7xxx series aluminum alloy, 8xxx series aluminum alloy, 9xxx series aluminum alloy; the particle reinforcement phase component is selected from one or more of TiB2, ZrB2, BN, B4C, SiC, TiC, WC, Al3BC, AlN, TiN, Si3N4, Al2O3, Y2O3, TiO2, SiO2, ZrO2, MgO, diamond.

3. The preparation method of a spherical powder of a particle-reinforced aluminum matrix composite material for laser 3D printing according to claim 1, characterized in that: In Step 1, the particle size of the pure aluminum or aluminum alloy matrix component powder is 1 to 15 μm, and the particle size of the particle reinforcement phase component powder is selected according to the material properties and does not exceed 20 μm.

4. The preparation method of the spherical powder of the particle-reinforced aluminum matrix composite material for laser 3D printing according to claim 1, characterized in that: In Step 1, the composition design mass ratio of the particle-reinforced aluminum matrix composite material is matrix component: particle reinforcement phase component = 10:90 to 99.5:0.

5.

5. The preparation method of a spherical powder of a particle-reinforced aluminum matrix composite material for laser 3D printing according to claim 1, characterized in that: In Step 2, the sintering atmosphere is nitrogen or argon containing trace oxygen.

6. The preparation method of the spherical powder of the particle-reinforced aluminum matrix composite material for laser 3D printing according to claim 1, characterized in that: In Step 3, the alkaline deoxidizer is an ethanol aqueous solution of sodium hydroxide, where the concentration of NaOH is 10 to 25 g / L, and the volume ratio of ethanol to water in the solvent is 1:9 to 3:

7.

7. The preparation method of the spherical powder of the particle-reinforced aluminum matrix composite material for laser 3D printing according to claim 1, wherein: In Step 3, the reaction temperature of the deoxidation treatment is 25 to 40 °C, and the deoxidation time is 8 to 30 min.

8. The preparation method of the spherical powder of the particle-reinforced aluminum matrix composite material for laser 3D printing according to claim 1, characterized in that: In Step 4, the pickling solution is nitric acid with a mass concentration of 15 to 35%, the pickling soaking temperature is 25 to 40 °C, and the treatment time is 0.5 to 2 minutes.

Citation Information

Patent Citations

  • Metal powder coated by high-molecular material, preparation method and application of metal powder

    CN110238388A

  • Preparation method of copper-based composite material powder for laser 3D printing

    CN117840437A